Adverse urinary effects of allopurinol in dogs with leishmaniasis. (26th April 2016) - Torres, M.; Pastor, J.; Roura, X.; Tabar, M. D.; Espada, Y.; Font, A.; Balasch, J.; Planellas, M.
Abstract : OBJECTIVE: The objective of this study was to describe the adverse effects of allopurinol on the urinary system during treatment of canine leishmaniasis. METHODS: Retrospective case series of 42 dogs that developed xanthinuria while receiving allopurinol treatment for leishmaniasis. RESULTS: Of 320 dogs diagnosed with leishmaniasis, 42 (13%) developed adverse urinary effects. Thirteen (of 42) dogs (31%) developed xanthinuria, renal mineralisation and urolithiasis; 11 (26·2%) showed xanthinuria with renal mineralisation; 9 (21·4%) had xanthinuria with urolithiasis and 9 (21·4%) developed xanthinuria alone. Urinary clinical signs developed in 19 dogs (45·2%). CLINICAL SIGNIFICANCE: This study demonstrates that urolithiasis and renal mineralisation can occur in dogs receiving allopurinol therapy. Dogs receiving therapy should be monitored for the development of urinary adverse effects from the beginning of treatment.